(untitled) (Ameghiniana, 2013)
The main purpose of this work is to describe a new fossil subfamily of ostracods, Rocaleberidinae, and three new genera which belong to it: Rocaleberis, Wichmannella and Neoveenia. The new subfamily is represented in surface sediments from the Roca (Lower Danian), Jagüel, Huantrai-co, Malargüe and Coli Toro (Lower and Middle Maastrichtian) Formations (Bertels, 1969). The type material is from the Roca Formation (Lower Danian) at its type locality Fortín General Roca (Rio Negro Province, Argentina). Within the microfaunistic assemblage of ostracods, the specimens included in the new subfamily constitute a high percentage of the whole of the fossil thanatocenosis belonging to this subclass; foraminifera, which were used for dating the marine sequences, were also found together with bryozoa, echinoid plates, etc. A summary of the features taken into account by different authors for the delimitation of the families Tracbyleberididae Sylvester-Bradley, 1948 and Hemicytheridae Puri, 1953, and their diagnosis are given, as well as the characters, that according to different author’s criteria should be taken into account for the delimitation of farnilies, subfamilies, genera and species. Brief comparisons of the new subfamily Rocaleberidinae follow each diagnosis, in the different sense given by various authors. The subfamily Rocaleberidinae is characterized in lateral view by a carapace with subrectangular outline, dorsal and ventrally subparallel, anterior margin broadly rounded, posterior rounded to obliquely rounded, dorsal margin straight, ventral concave; ovate in dorsal view; extremities with rows of small tubercules or denticulations; eye tubercules and eye sinus clearly developed; subcentral node present or only revealed by strongly reticulation or by an anular depression; subcentral muscle scar pattern in a low depression formed by four from the adductor, from which the upper dorsal is divergent respect to the other three, two ventrals partially superposed, frontal in V. U. J or heart shape; inner calcareous Iarnella moderately wide with inner margin and concrescence line not coincident, vestibule always present; marginal zone with sparce or in a modera te number of marginal pore canals, straight, simple or branched; submarginal pores present; normal pore canals open, big, sparce; hinge amphidont; sexual dimorphism strongly developed. Rocaleberis n. gen. is characterized in lateral view by a carapace subrectangular in shape, anterior and posterior extremities rounded; ovate in lateral view; ocular tubercule pronounced, eye sinus present, post-ocular depression marked, subcentral swelling developed; primary surface ornamentation with three low longitudinal foldings and reticulations, superimposed by small tubercules or spines. W ichmannella n. gen. is characterized by its subrectangular carapace outline shape in lateral view, anterior broadly rounded, posterior somewhat obliquely rounded; ovate in dorsal view; eye tubercule and eye sinus present, post ocular depression marked; subcentral node insinuated by a light annular depression; primary ornamentation consisting of reticulations, arranged more or less parallel to the peripherie, superimposed sometimes by sparced tubercules at the reticulum intersections. Neoveenia n. gen. shows in lateral view a sub rectangular to subtrapezoidal carapace outline shapc, dorsal straight, ventral slightly convex, anterior bluntly rounded, posterior obliquely rounded originated by the prolongation from the ventral border to the dorsal at the posterior cardinal extremity; ovate in dorsal view; dorsal margin straight, ventral concave; eye tubercule markedly developed, post ocular depression and eye sinus present, primary ornamentation with three longitudinal foldings that do not reach the valve extremities, and reticulations. Phylogenetieally, by the morphologieal features of the earapaee, the author’s idea is that the new subfarnily is an intermediate group between the Tracbyleberididae and Hemicytberidae in the sense of the Treatise (Moore, 1961); from the Trachyleberidinae and Hemicytberinae in van Morkhoven’s (1962-63) sense and/cr from the subfamilies Tracbyleberidinae and Campylocytherinae or Tracbyleberidinae and Ecbinocytherinae in the sense of Hazel (1967 a) in virtue of the muscle sear pattern and external features, sueh as shape. Some primitive features from the new subfamily could be the parcial fusion of the outer with the inner ealcareous lamella, the big normal pore eanals, open and sparce; in the same sense the subeentral muscle sear pattern could be taken as primitive in the case that the group is really intermedia te from both subfamilies and originated from a racbyleberidinae ancestcr. The new genus Rocaleberis from the Paleocene of Argentina shows similarities with Haryboioella Puri, 1957 which appears in the Mioeene; if the duplieature not completely fused is a primitive feature, Rocaleberis could be the aneestor - not neeessarily a direct one- of Henryhowella; the evolutionary change eould be the complete fusion of the outer with the inner calcareous lamella and the reduction in size of the normal pore canals. The genus Wicbmannella shows affinities with Ecbinocvtbereis Puri, 1954 whieh appears in the Eoeene; phylogenetieally it eould be a split of the frontal sear, the aequisition of a eompletely fused duplieature and the reduetion in size of the normal pore canaIs. The genus Neoveenia phylogenetically shows to be more related in external features, sueh as shape, with Protocytbere Triebel, 1938 and Veenia Butler & Jones, 1957, both from the Cretaeeous. Internal features, like hingement and duplieature show however important differences. Comparisons and suggested phylogenetic trends made independentelly for each genus sppear logic and possible, but seen as a whole, we are dealing with genera with eomon features, with an homogeneous group belonging to one subfamily; consequently rt seems Improbable that Protocytbere or Veenia eould be the ancestors of the new subfamily Rocaleheridinae, since its ascendency on the new genera Rocaleberis and Wicbmannella would split the new subfamily into two or three phylogenetic branehes to give rise to Henryboioella and Ecbinocytbereis respectively - if they are related -, aecording to the present sistematic schemes.